COVID‐19 crisis and risk spillovers to developing economies: Evidence from Africa. (21st February 2022) - Akhtaruzzaman, Md; Benkraiem, Ramzi; Boubaker, Sabri; Zopounidis, Constantin
Abstract: This study provides new evidence on how risk spillovers occur from the United States to developing economies in Africa during the COVID‐19 pandemic. The results show that downside risk exposures of African markets, financial firms and banks particularly increased during Phase I (30 January to 30 April 2020). The nature and magnitude of downside risk exposures of African financial markets were similar to those of the United States. Our results also reveal that the United States is a net transmitter of risk spillovers while Nigeria, South Africa, Egypt and Morocco are net recipients. Our conclusions offer guidance to risk managers, policymakers and investors.